RELEASING SERVICES TO PEOPLE SICK DUE TO OCCULTISM - Jusuf Hutapea; Jose Abraham (MAHABBAH: Journal of Religion and Education, 2021)
Occult forces made them physically sick for years. They are formed by fear, discomfort and also they lose touch with God or don't grow spiritually. The occult always damages human life physically and mentally. This writing uses a descriptive qualitative method with a practical theological approach with several case studies. This article aims to describe how the ministry can serve the people concerned who are affected by the effects of darkness (occult). Correct recovery services can help free people affected by occultism.